Tourism and intercultural communication and innovations - Rafailova, Genka; Marinov, Stoyan (Cambridge Scholars Publishing, 2019)
This volume presents the results of Bulgarian and international tourism research, and brings together selected papers from the international conference ""Tourism and Innovations"" held in Varna, Bulgaria, in 2018. It contains theoretical and empirical approaches towards various aspects of tourism concerning both innovations in tourism development and in foreign languages education. As a whole, the book presents innovative solutions and processes in tourism, including management and staff training, provoked by today's opportunities and challenges for future tourism development. The first part i.